Experimental study on the mechanical properties of modified phosphogypsum at different loading rates - Bo Zhang; Chaohua Xu; Qin Wu; Xiaohui Qin; Jiagang Wei; Zhen Lu (Scientific Reports)
Abstract Phosphogypsum is the main industrial solid waste from wet process phosphoric acid production, which has significant potential for environmental sustainability and engineering applications when modified. In order to explore the mechanical properties of modified phosphogypsum (MG) in different loading environments, uniaxial compression tests were conducted at four loading rates: 0.03, 0.06, 0.12, and 0.6 mm/min. The test results show that MG undergoes creeping at the loading rate of 0.03 mm/min, quasi-static loading at 0.12 to 0.6 mm/min, and transition between the two states at 0.06 mm/min. As the loading rate increases, the crack initiation stress $${σ _{{\text{ci}}}}$$ , damage stress $${σ _{{\text{cd}}}}$$ , and peak strength $${σ _f}$$ gradually increase, but the increasing amplitude gradually decreases. Under quasi-static loading at 0.12 to 0.6 mm/min, $${σ _{{\text{ci}}}}{\text{/}}{σ _f}$$ and $${σ _{{\text{cd}}}}{\text{/}}{σ _f}$$ show no significant changes and remain at 0.52 and 0.81, respectively, close to the values of rock materials. As the loading rate increases from creep loading to quasi-static loading, the elastic strain energy increases slowly and steadily, while the total strain energy and dissipative strain energy decrease first and then increase slowly. With the axial stress increasing from 0 to 0.81 $${σ _f}$$ , the principal strain field changes from relatively uniform to a concentration band, which has a very steep angle with the horizontal direction. The research results provide an important theoretical basis for the engineering application of MG as building materials.